Bourdieu's Politics: Problems and Possibilities - Jeremy F. Lane (Routledge, 2006)
In the last decade of his career, the French sociologist Pierre Bourdieu became involved in a series of high-profile political interventions, defending the cause of striking students and workers, speaking out in the name of illegal immigrants, the homeless and the unemployed, challenging the incursion of the market into the field of artistic and intellectual production.